Navigating between Scylla and Charybdis: challenges and strategies for implementing guideline‐directed medical therapy in heart failure with reduced ejection fraction. (13th December 2021) - Seferović, Petar M.; Polovina, Marija; Adlbrecht, Christopher; Bělohlávek, Jan; Chioncel, Ovidiu; Goncalvesová, Eva; Milinković, Ivan; Grupper, Avishay; Halmosi, Róbert; Kamzola, Ginta; Koskinas, Konstantinos C.; Lopatin, Yuri; et al.
Abstract: Guideline‐directed medical therapy (GDMT) has the potential to reduce the risks of mortality and hospitalisation in patients with heart failure (HF) with reduced ejection fraction (HFrEF). However, real‐world data indicate that many patients with HFrEF do not receive optimised GDMT, which involves several different medications, many of which require up‐titration to target doses. There are many challenges to implementing GDMT, the most important being patient‐related factors (comorbidities, advanced age, frailty, cognitive impairment, poor adherence, low socioeconomic status), treatment‐related factors (intolerance, side‐effects) and healthcare‐related factors that influence availability and accessibility of HF care. Accordingly, international disparities in resources for HF management and limited public reimbursement of GDMT, coupled with clinical inertia for treatment intensification combine to hinder efforts to provide GDMT. In this review paper, authors aim to provide solutions based on available evidence, practical experience, and expert consensus on how to utilise evolving strategies, novel medications, and patient profiling to allow the more comprehensive uptake of GDMT. Authors discuss professional education, motivation, and training, as well as patient empowerment for self‐care as important tools to overcome clinical inertia and boost GDMT implementation. We provide evidence on how multidisciplinary care and institutional accreditation can be successfully used to increase prescription rates and adherence to GDMT. We consider the role of modern technologies in advancing professional and patient education and facilitating patient–provider communication. Finally, authors emphasise the role of novel drugs (especially sodium–glucose co‐transporter 2 inhibitors), and a tailored approach to drug management as evolving strategies for the more successful implementation of GDMT.